O lugar do fandom no processo produtivo das indústrias culturais no contexto da cultura da convergência: os casos de "Doctor Who Brasil" e "Universo Who" - Vieira, Eloy Santos (2016)
This research aims to point which would the place that fandoms could occupy inside the production process managed by culture industries inside the convergence culture context. So, we chose the Brittish TV Show “Doctor Who” as a starting point because it has a lot of features of the convergence culture presented by the authors we used and also because of its longevity and adaptability during all these 50 years on air. Then, we bring up the concept of convergence culture based on Aquino (2012) who proposes a theoretical triad ir order to comprehend this issue: technology, society and culture. So, we add the economic feature to her statement through an approach that values the “Theoretical Interdisciplinarity” (KLEIN, 2010) intending to include a general overview. Only after that we come up with a generic model that includes fans and, at last, we chose two of the biggest Brazilian fandoms to instace this model. A content analys based on the entire production of both groups in Twitter during November 2013 was made. This was the period when the Doctor Who 50-year anniversary was emphasized by BBC and it was inside Twitter that Brazilian fans respondend to that when they got mobilized for the annyversary especial showing at the movies. So, through a combination of content analysis (BARDIN, 1995) and interviews with the fandom leaders, we could find that the generic model could be applicable in both specific cases and thet the cultural industries players hás been proposing new strategies that, at the same time, pitch in with the maintenance of a productive cicle managed by them but also opens to fandom a role as an intermediary instance capable of guide the consumption of the other audiences.